Strength abilities: assessment of cumulative training effects of strength loads of a series of classes in 8 years old boys - Iermakov, S.; Ivashchenko, O.; Khudolii, O. (Journal of Physical Education and Sport, 2021)
The purpose of the study wasto determine the impact of orthogonal strength loads on the dynamics of cumulative training effects of a series of classes in 8 years old boys. Materials and methods.The study participants were 48 boys 8 years old. The experiment was conducted using a 22 factorial design. The study materials were processed by the IBM SPSS 22 statistical analysis program. Discriminant analysis was performed. The study examined the impact of four variants of strength load onthe formation of the cumulative training effect of a series of classes in 8 years old boys. Results.The study obtained data on the informativeness of canonical functions in assessing the cumulative training effect of strength loads, and carried out their verification. Structure coefficients and group centroids for the 1st-4thvariants of strength load were analyzed. The discriminant analysis made it possible to obtain information about the dynamics of the cumulative training effect of strength exercises with different focuses, taking into account their modes after 3, 6, 9, and 12 classes. Conclusions. It is possible to classify the cumulative training effect of a series of classes based on discriminant analysis. The effectiveness of discriminant analysis increases with the use of active 2k full factorial experiments. The verification of the obtained discriminant functionsshows their high discriminative ability and value in interpretation with respect to the general population(p < 0.05). The analysis ofstructure coefficients showedthe most significant changes in the CTE after work at places 1-4, the analysis of group centroids- the impact of strength loadson the dynamics of the CTE after 3, 6, 9, and 12 classes.In boys 8 years old, the cumulative training effect of strength exercises after 3, 6, 9, and 12 classes as compared with the initial level differs statistically significantly and has different focuses: variant I - strengthening arms, abdominal muscles, and leg muscles; variant II - strengthening abdominal,back, and leg muscles; variant III - strengthening abdominal muscles; variant IV - strengthening all muscles. The greatest overallpositive effect is observed in: variants I and II - after 9 classes; variant III - after 3 classes; variant IV - after 6 classes.